PROSPECTS OF CONSTRUCTIVE THINKING IN THE CONTEXT OF DIGITAL CIVILIZATIONS - Gulnoza Sabirovna Sultanova (Web of Journals Publishing, 2025)
This paper explores the prospects of constructive thinking in the era of digital civilizations. Constructive thinking defined as the ability to analyze deeply, synthesize knowledge, and generate innovative solutions—has become essential in contemporary education and society. The study reviews theoretical foundations, empirical findings, and practical examples to demonstrate how digital technologies can enhance cognitive and non-cognitive capacities. Challenges such as information overload, superficial processing, and reduced critical reflection are discussed. The paper also proposes pedagogical strategies, including project-based learning, adaptive digital platforms, and interactive environments, to cultivate constructive thinking skills. Finally, future research directions and implications for digital education policy are outlined.
Keywords: Constructive thinking; digital civilization; cognitive development; innovation; education; pedagogy; adaptive learning.